2010
DOI: 10.1016/j.neuroimage.2010.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Harsh corporal punishment is associated with increased T2 relaxation time in dopamine-rich regions

Abstract: Harsh corporal punishment (HCP) was defined as frequent parental administration of corporal punishment (CP) for discipline, with occasional use of objects such as straps, or paddles. CP is linked to increased risk for depression and substance abuse. We examine whether long-term exposure to HCP acts as sub-traumatic stressor that contributes to brain alterations, particularly in dopaminergic pathways, which may mediate their increased vulnerability to drug and alcohol abuse. Nineteen young adults who experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 79 publications
3
36
0
3
Order By: Relevance
“…Chronic stress increases the state of alertness [59], which is associated with the thalamus [58]. Consistent with our result, a Positron Emission Tomography study [60] revealed significantly greater regional cerebral glucose metabolism in thalamus in adult monkeys who experienced early life stress compared to controls, and another study [61] showed that young adults who experienced corporal punishment in childhood exhibited increased cerebral blood volume in the thalamus. Greater activation or increased volumes in the thalamus might suggest a general problem with sensory information processing, perhaps indicating hyper-vigilance, which is thought to be involved in the pathophysiology of GAD.…”
Section: Discussionsupporting
confidence: 87%
“…Chronic stress increases the state of alertness [59], which is associated with the thalamus [58]. Consistent with our result, a Positron Emission Tomography study [60] revealed significantly greater regional cerebral glucose metabolism in thalamus in adult monkeys who experienced early life stress compared to controls, and another study [61] showed that young adults who experienced corporal punishment in childhood exhibited increased cerebral blood volume in the thalamus. Greater activation or increased volumes in the thalamus might suggest a general problem with sensory information processing, perhaps indicating hyper-vigilance, which is thought to be involved in the pathophysiology of GAD.…”
Section: Discussionsupporting
confidence: 87%
“…This approach has been useful in revealing similarities and differences between the neurobiological correlates of exposure to childhood sexual abuse [48,57], parental verbal abuse [11,51], WDV [8] and harsh corporal punishment [12,58]. This strength is also a limitation as many abused individuals, particularly those involved in the mental health system, experienced multiple forms of maltreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Corporal punishment negatively affects the internalization of moral values by the child and his relationship with his parents [15]. Physical punishment is linked to a slow regression of cognitive development as well as negative effects on the academic pathway [1620], noncognitive performance and executive functions [21] as well as alterations in the dopaminergic regions associated with substances and alcohol abuse [22]. In particular, negative experiences in childhood predispose later in life, to multiple sexual partners, sexually transmitted diseases, teenage pregnancies, unwanted pregnancies, and early initiation of sexual activity [23].…”
Section: Introductionmentioning
confidence: 99%